A Role for Glutathione Transferase Omega 1 (GSTO1-1) in the Glutathionylation Cycle - Menon, Deepthi; Board, Philip G. (The Journal of biological chemistry, 2013)
The glutathionylation of intracellular protein thiols can protect against irreversible oxidation and can act as a redox switch regulating metabolic pathways. In this study we discovered that the Omega class glutathione transferase GSTO1-1 plays a significant role in the glutathionylation cycle. The catalytic activity of GSTO1-1 was determined in vitro by assaying the deglutathionylation of a synthetic peptide by tryptophan fluorescence quenching and in T47-D epithelial breast cancer cells by both immunoblotting and the direct determination of total glutathionylation. Mutating the active site cysteine residue (Cys-32) ablated the deglutathionylating activity of GSTO1-1. Furthermore, we demonstrate that the expression of GSTO1-1 in T47-D cells that are devoid of endogenous GSTO1-1 resulted in a 50% reduction in total glutathionylation levels. Mass spectrometry and immunoprecipitation identified β-actin as a protein that is specifically deglutathionylated by GSTO1-1 in T47-D cells. In contrast to the deglutathionylation activity, we also found that GSTO1-1 is associated with the rapid glutathionylation of cellular proteins when the cells are exposed to S-nitrosoglutathione. The common A140D genetic polymorphism in GSTO1 was found to have significant effects on the kinetics of both the deglutathionylation and glutathionylation reactions. Genetic variation in GSTO1-1 has been associated with a range of diseases, and the discovery that a frequent GSTO1-1 polymorphism affects glutathionylation cycle reactions reveals a common mechanism where it can act on multiple proteins and pathways. Background: Glutathionylation is a major post-translational modification that regulates protein function. Results: Human glutathione transferase Omega 1 (GSTO1-1) can catalyze the deglutathionylation of protein thiols in vitro and in cell culture. Conclusion: GSTO1-1, but not GSTO2-2, catalyzes the deglutathionylation of actin and other proteins under physiological conditions. Significance: Genetic variation in GSTO1-1-catalyzed deglutathionylation may influence the function of multiple proteins in signaling pathways.